Experimental investigation on the coupling between immersion rig and tunnel element during freeboard elimination. (15th August 2019) - Huang, Guoxing; Song, Yue; Sun, Zhenxiang; Zhang, Ningchuan
Abstract: This study aims to investigate the coupled mechanism of the tunnel immersion system during freeboard elimination, one of the most critical scenarios for submerged tunnel construction. To address the coupling effect, synchronous measurements have been conducted on the tunnel/rig motions and the suspension tensions during freeboard elimination. The motion characteristics of the tunnel at zero-freeboard and immersion rigs are compared under regular and random waves. The effects of the wave period, wave height and wave obliquity on the dynamic responses of the system are examined. The results indicate that the coupling effect between the tunnel and rig is not only subjected to the wave height, but also the wave period. In particular, the most critical downward displacement of the tunnel and suspension tension were observed at the natural roll period of the coupled system T  =  T roll . In addition, green water has a significant effect on the downward displacement of the tunnel and leads to severe relative heave and critical dynamic suspension tensions.